Reciprocity between mediation and judicial reorganization:: the importance of the party autonomy’s principle in reducing damages caused by the new Coronavirus pandemic - Mariotini, Fabiana (2021)
This paper proposes to analyze the contractual renegotiation, especially in judicial reorganizations, in the Coronavirus pandemic scenario. Therefore, the main aspects regarding this subject will be highlighted, including historical and evolutive issues. After examining the filigrees referring to the rebalance of the contracts and party autonomy, a path will be built to point that mediation is an ideal place to foster social pacification in such context. The bibliographic review method is used to construct the premises of the study, and the deductive method is used in the formulation of the theses defended.